Effects of marginal umbilical cord insertion on the prognosis of fetus - Y. Tian; H. Luo; M. He (Clinical and Experimental Obstetrics & Gynecology)
Objective: To investigate the effect of marginal placental insertion of the umbilical cord on the prognosis of a fetus. Material and Methods: Retrospective analysis was performed to compare the differences in fetal weight (FW), placental weight (PW), fetal/placental weight ratio (FPR) and complications between 295 cases with marginal insertion of umbilical cord, and 297 cases with normal umbilical cord insertion. The cases studied, with marginal insertion of umbilical cord, were admitted between 2013-2017 to the Second Western China Hospital of Sichuan University. The cases were divided into “upper”, “lower” and “other”, according to the site of umbilical cord insertion into the placenta. Results: The FW was lower, while the incident of low-birth weight infants was higher in the marginal umbilical cord insertion group than in the normal umbilical cord insertion group. In the subgroup of lower marginal insertions, the PW and FW were lower and the FPR was higher than in the subgroup of upper marginal insertion sites.Conclusion: The fetus with lower marginal umbilical cord insertion should be attended closely, with frequent monitoring of the developmental indices in order to screen abnormal growth of the fetus.